2008
DOI: 10.4103/0970-0218.39239
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to blood and body fluids among health care workers in a teaching hospital in Mumbai, India

Abstract: Objective:Exposure to blood and body fluids is one of the hidden hazards faced by health care workers (HCWs). The objective of the present study was to estimate the incidence of such exposure in a teaching hospital.Materials and Methods:A cross-sectional study among a random sample of residents, interns, nurses and technicians (n = 830) was carried out in a teaching hospital to estimate the incidence of exposure to blood and body fluids in the preceding 12-month period. Self-reported occurrence and the circums… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 12 publications
1
16
3
Order By: Relevance
“…Also they specified six types of sharps lead to stick injuries including hypodermic needles, suture needles, butterfly, scalpel blades, IV catheter and phlebotomy needles. Also Hashmi et al (2012) [37] and Singru and Banerjee (2008) [38] showed that the highest incidence of occupational exposure was among nurses especially novice ones and only half of these incidents were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Also they specified six types of sharps lead to stick injuries including hypodermic needles, suture needles, butterfly, scalpel blades, IV catheter and phlebotomy needles. Also Hashmi et al (2012) [37] and Singru and Banerjee (2008) [38] showed that the highest incidence of occupational exposure was among nurses especially novice ones and only half of these incidents were reported.…”
Section: Discussionmentioning
confidence: 99%
“…In Sub-Saharan countries exposure of NSSIs is higher than elsewhere and becoming a significant public health issue due to the fear of occupational infections faced by ill paid, ill protected and overworked HCWs. It accounts for 86% of all occupationally related infection transmissions and causes 1000 infections per year [7,8]. The Centers for Disease Control and Prevention also estimates that HCWs sustain approximately 385,000 sharps-related injuries annually [9].…”
Section: Introductionmentioning
confidence: 99%
“…1 These preventable injuries expose healthcare workers to over 20 different blood borne pathogens, and resulted in 1000 infections per year. 2 Needle stick injury accounted for 86% of all occupationally related infection transmissions. The most common blood borne pathogens transmitted with NSIs are hepatitis B, hepatitis C and HIV.…”
Section: Introductionmentioning
confidence: 99%